Photon-induced multiple particle emissions of Zr90 and natZr from 10 to 140 MeV - Rodrigues, T. E.; Martins, M. N.; Garcia, C.; Arruda-Neto, J. D T; Mesa, J. [UNESP]; Shtejer, K.; Garcia, F. (American Physical Society (APS), 2007)
A comprehensive analysis of electrodisintegration yields of protons on Zr90 is proposed taking into account the giant dipole resonance, isovector giant quadrupole resonance (IVGQR), and quasideuteron contributions to the total photoabsorption cross section from 10 to 140 MeV. The calculation applies the MCMC intranuclear cascade to address the direct and pre-equilibrium emissions and another Monte Carlo-based algorithm to describe the evaporation step. The final results of the total photoabsorption cross section for Zr90 and relevant decay channels are obtained by fitting the (e,p) measurements from the National Bureau of Standards and show that multiple proton emissions dominate the photonuclear reactions at higher energies. These results provide a consistent explanation for the exotic and steady increase of the (e,p) yield and also a strong evidence of a IVGQR with a strength parameter compatible with the E2 energy-weighted sum rule. The inclusive photoneutron cross sections for Zr90 and natZr, derived from these results and normalized with the (e,p) data, are in agreement within 10% with both Livermore and Saclay data up to 140 MeV. © 2007 The American Physical Society.